Sustainability indicators: at the bottom line of institutional relevance - Cain, Kelly (My University, 2010)
Article by Dr. Kelly Cain (University of Wisconsin-River Falls) which examines sustainability performance indicators. The article appeared in the AASHE Campus Sustainability Perspectives Blog on May 18, 2010.
2 p.
Keywords: Sustainability indicators; Campus planning--Environmental aspects--United States; Environmental impact analysis; Sustainable development; College campuses--Environmental aspects--United States; Universities and colleges--Environmental aspects--United States; Sustainability tracking, assessment and rating system; STARS; Sustainability; Environmental management; Community development; Sustainable community development